2005
DOI: 10.1099/vir.0.80635-0
|View full text |Cite
|
Sign up to set email alerts
|

Human immunodeficiency virus 1 (HIV-1) envelope-dependent cell–cell fusion modulation by HIV-positive sera is related to disease progression

Abstract: Fusion of CD4+ cells by HIV-1 envelope proteins (Env) is a mechanism of virus spread and cell damage. Production of antibodies able to influence cell-cell fusion in vivo may affect the course of the infection. The effect of sera from 49 HIV-1-positive patients was tested on an in vitro fusion assay using Env-expressing and normal Jurkat T cells labelled with DiI and DiO dyes, and flow cytometry for quantification of cell-cell fusion. Sera varied in their activity on fusion: 69?4 % inhibited, 24?5 % had no effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…The results of those immunizations were basically negative despite the presentation of the ELDKWAS (or some longer sequence) peptide on various vectors and the inclusion of a fusion peptide sequence [45] and lipids [46] as parts of the viral structures to optimize the 2F5 antigenic function (see [37] for exhaustive critical analysis of this item). Using a cell-cell fusion system, which was proven to be highly sensitive to inhibitors in our previous experiments [31][32][33][34][35] against 2F5 in this study, we found that mouse antiserum to the both the linear and constrained peptides did not affect fusion while the rabbit antiserum to the linear but not to the constrained peptide decreased fusion by approximately 50% and to 20% at 1:10 and 1:100 dilutions, respectively. Inhibition by mAb 2F5 was not observed in the presence of the 15-mer ELDKWAS-containing peptide competitor of the epitope (Fig.…”
Section: Immunogenic Potential Of the Described Linear And Constrainementioning
confidence: 79%
See 2 more Smart Citations
“…The results of those immunizations were basically negative despite the presentation of the ELDKWAS (or some longer sequence) peptide on various vectors and the inclusion of a fusion peptide sequence [45] and lipids [46] as parts of the viral structures to optimize the 2F5 antigenic function (see [37] for exhaustive critical analysis of this item). Using a cell-cell fusion system, which was proven to be highly sensitive to inhibitors in our previous experiments [31][32][33][34][35] against 2F5 in this study, we found that mouse antiserum to the both the linear and constrained peptides did not affect fusion while the rabbit antiserum to the linear but not to the constrained peptide decreased fusion by approximately 50% and to 20% at 1:10 and 1:100 dilutions, respectively. Inhibition by mAb 2F5 was not observed in the presence of the 15-mer ELDKWAS-containing peptide competitor of the epitope (Fig.…”
Section: Immunogenic Potential Of the Described Linear And Constrainementioning
confidence: 79%
“…The cell-cell fusion protocol developed by Huerta et al [31] and subsequently extensively employed by Huerta et al [32], López-Balderas et al [33], Huerta et al [34], Rivera-Toledo et al [35] was used in these experiments to test the anti-mimotope serum antibodies. The protocol involves labeling fusion partner cells with the fluorescent carbocyanines DiI and DiO (Molecular Probes).…”
Section: Cell Culture and Cell-cell Fusion Assaysmentioning
confidence: 99%
See 1 more Smart Citation
“…We explored the effect of sera from HIV-infected individuals on the fusion of Env + and CD4 + Jurkat cells [103]. Most (69%) of the sera from a sampling of 49 HIV-positive individuals inhibited fusion to some extent; 24.5% had no effect and 6.1% enhanced fusion.…”
Section: Association Of Effect Of Sera On Fusion With Markers Of Hiv mentioning
confidence: 99%
“…Cell-cell fusion assays are attractive tools for identifying potent inhibitors of HIV-1 Env function. Such assays mimic the entry steps of HIV-1 into cells, and can measure membrane-fusing activity, as well as its inhibition, with high sensitivity [43], [44], [45], [46], [47], [48], [49], [50], [51], [52]. The assay also simulates the multiple Env-receptor interactions that occur during direct transmission of the virus from one cell to another, and offers a unique system to study and potentially inhibit this mode of transmission [53], [54], [55].…”
Section: Introductionmentioning
confidence: 99%